Cyber-Archaeometry: Novel Research and Learning Subject Overview - Ioannis Liritzis; Pantelis Volonakis (MDPI AG, 2021)
The cyber archaeometry concerns a new virtual ontology in the environment of cultural heritage and archaeology. The present study concerns a first pivot endeavor of a virtual polarized light microscopy (VPLM) for archaeometric learning, made from digital tools, tackling the theory of mineral identification in archaeological materials, an important aspect in characterization, provenance, and ancient technology. This endeavor introduces the range of IT computational methods and instrumentation techniques available to the study of cultural heritage and archaeology of apprentices, educators, and specialists. Use is made of virtual and immersive reality, 3D, virtual environment, massively multiplayer online processes, and gamification. The VPLM simulation is made with the use of Avatar in the time-space frame of the laboratory with navigation, exploration, control the learning outcomes in connection to the archaeometric multisystem work. The students evidently learned to operate the VPLM following operations made via visual and home-made scripting, gaining experience in synergy, teamwork, and understanding. The resulting meaningful effects of the cyber-archaeometry with virtual operations and virtual hands, texts, and video equip students especially for e-learning with the required basic knowledge of mineralogical examination, which help to understand and evaluate mineral identification from material culture and provides readiness and capacity, which may be refined in a real polarized light microscopy (PLM) environment.